ICT Systems Security and Privacy Protection: 33rd IFIP TC 11 International Conference, SEC 2018, Held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, Proceedings - Janczewski, Lech Jan; Kutyłowski, Mirosław (ICT Systems Security and Privacy Protection 33rd IFIP TC 11 International Conference, SEC 2018, Held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, Proceedings, 2018)
This book constitutes the refereed proceedings of the 33rd IFIP TC 11 International Conference on Information Security and Privacy Protection, SEC 2018, held at the 24th IFIP World Computer Congress, WCC 2018, in Poznan, Poland, in September 2018.The 27 revised full papers presented were carefully reviewed and selected from 89 submissions.